Skateboarding injuries in Spain: a web-based survey approach - Rodríguez-Rivadulla, A.; Saavedra-García, M. A.; Arriaza-Loureda, R. (Orthopaedic Journal of Sports Medicine, 2020)
Background: The inclusion of skateboarding in the Tokyo 2020 Olympic Games reinforces this activity as a sport. As the number of skateboarders around the world and the difficulty of skateboarding maneuvers continue to increase, the number of skateboarding injuries may also rise. Thus, there is a need for more comprehensive investigations into the practice habits and injuries of skateboarders.